Real Queer: "Authentic" LGBT Refugee Claimants and Homonationalism in the Canadian Refugee System - Murray, David A. B. (Anthropologica, 2014)
Since the early 1990s, Canada has become a primary destination for individuals who make refugee claims on the basis of sexual orientation persecution. Based on interviews with lesbian, gay, bisexual and transgender (LGBT) identified refugee claimants, social workers and refugee lawyers in Toronto, I argue that LGBT refugees and those who work with them are enmeshed in a system predicated upon highly malleable, historically and socio-politically specific sexual terms and identities that privilege particular gendered, classed and raced interests and, thus, place LGBT refugees from non North American societies in a particularly vulnerable position.